MENGIDENTIFIKASI PROSES PEMBELAJARAN IPA SISWA KELAS IV DI SD NEGERI TALABIU PADA MASA PANDEMI COVID-19 - Faridah, Fifi; Salahudin, Salahudin; Mariamah, Mariamah; Ajwar, Muhamad (Tunas: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of this study was to find out the science learning carried out for fourth grade students at SDN Talabiu for the 2020/2021 academic year during the Covid-19 period. This type of research is a qualitative research with a descriptive approach where the researcher emphasizes on humans and sees firsthand the existing situation without changing the events that occur in the field. As for the subject in this study is the learning activities of class IV students. The main instrument used in this study were interviews and direct observation of activities carried out in the learning process. The results of the interview will be analyzed qualitatively through several stages starting from data reduction activities, data display, and conclusions or verification. The results showed that the learning process was carried out for fourth grade students at SDN Talabiu. At the beginning of the Covid-19 outbreak, the school had used the online method, by means of a WA group. But it turns out that using the online system or studying at home is not effective, the ineffectiveness can be seen from the students themselves who do not understand how to use the application, and finally schools are closed. After Covid-19 was seen to be preventable by complying with health protocols, schools were active again by using rules or offline (face-to-face) methods. But still comply with health protocols, and use a shift learning system.